An Analysis of the Use of Animated Video Media on the Learning Interest of Grade XI Students in the Subject of Creative Products and Entrepreneurship at SMK Al-Hidayah Ciputat - Hasanah; Mulqiyah; Rusmaini, (International Journal of Economics Education Research (IJEER), 2025)
This study aims to analyze the use of animated video media in enhancing the learning interest of 11th-grade students in the subject of Creative Products and Entrepreneurship at SMK Al-Hidayah Ciputat. The research is motivated by the low learning interest among students, which is attributed to monotonous conventional teaching methods and limited use of varied instructional media. Employing a literature review method with a qualitative approach, this study examines both primary and secondary sources to evaluate the effectiveness of animated video media in educational contexts. The findings indicate that animated video media significantly captures students' attention, facilitates comprehension of abstract concepts, and fosters an engaging and interactive learning environment. Through visually appealing content and clear presentation, animated videos have been proven to increase students’ motivation and interest in learning, contributing to a more effective and meaningful learning experience.